2020
DOI: 10.1002/jlb.2mr1219-233r
|View full text |Cite
|
Sign up to set email alerts
|

αβ and γδ T cell receptors: Similar but different

Abstract: There are 2 populations of T lymphocytes, αβ T and γδ T cells, that can be distinguished by the expression of either an αβ TCR or a γδ TCR, respectively. Pairing of the Ag binding heterodimer, which consists of TCR‐α/TCR‐β (TCRαβ) or TCR‐γ/TCR‐δ (TCRγδ), with proteins of the CD3 complex forms the complete αβ or γδ TCR. Despite some similarities in the structure of TCRαβ and TCRγδ and the shared subunits of the CD3 complex, the 2 receptors differ in important aspects. These include the assembly geometry of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 102 publications
(227 reference statements)
1
59
0
Order By: Relevance
“…Since both CD3 and anti-TRBC1 antibodies recognize physically close epitopes of the CD3/TCRαβ complex [36,37], we first tested the potential steric interaction between both groups of antibody reagents for optimization of the TRBC1 staining. Our results showed…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since both CD3 and anti-TRBC1 antibodies recognize physically close epitopes of the CD3/TCRαβ complex [36,37], we first tested the potential steric interaction between both groups of antibody reagents for optimization of the TRBC1 staining. Our results showed…”
Section: Discussionmentioning
confidence: 99%
“…Since both CD3 and anti-TRBC1 antibodies recognize physically close epitopes of the CD3/TCRαβ complex [36,37], we first tested the potential steric interaction between both groups of antibody reagents for optimization of the TRBC1 staining. Our results showed that addition of CD3 blocked the (low affinity/unspecific) binding of the anti-TRBC1 reagent to TRBC1 − (i.e., TRBC2 + ) Tαβ-cells [38], while similar percentages of TRBC1 + cells were observed in the absence vs. presence of the CD3 Mab.…”
Section: Discussionmentioning
confidence: 99%
“…27 and refs. therein), although some distinctions in CD3 heterodimers, FceRIγ and CD3ζ composition, may further tune signaling (53)(54)(55)(56). Replacement of CγCδ in WTDP10.7 γδTCR with CαCβ in the γδ-αβTCR construct confers αβTCR mechanosensing properties to the chimeric receptor whose VγVδ module (i.e., ligand interaction surface) remains the same.…”
Section: Discussionmentioning
confidence: 99%
“…Its receptors comprise ligand-binding subunit variants differing in their capacity to amplify bioforces and thus to modulate triggering of cellular activation using a comparable set of signaling (CD3) subunits. Other distinctions between TCRαβ and TCRγδ, including their connecting peptides and transmembrane segments (56), in addition to their ectodomains, might further nuance signaling differences.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the potential as a therapeutic target, CD8 + TCR repertoire dynamics and the modulation mechanisms of chemotherapy are still poorly understood. αβ T cells are the predominant subset, making up approximately 90-95% of all peripheral T cells in healthy adults [16]. Therefore, it is crucial to assess the characteristics of the CD8 + TCR repertoire and investigate the clinical signi cance in AML patients.…”
Section: Introductionmentioning
confidence: 99%